MAKE WASTE BECOME FEAST - A Business Plan Addressing the Food Waste Problem in China - Wu, Jiang (2018)
Food plays an essential role in everyone’s life. In Maslow’s hierarchy of needs, food is categorized at the most fundamental level with other vital factors such as breathing, water, and sleep (McLeod, 2018). Without food, we will not be able to study, work, travel or proceed any further tasks. With the economic development, as people have more disposable income than ever before, most of us don’t suffer from food security. However, astonishing facts still exist worldwide, and tragedy happens every day. According to the study of World Food Program (2015), there are up to 800 million people do not have enough food to live a healthy life, and a quarter of the world’s children are undernourished. Even though we may not suffer hunger by ourselves, we should pay attention to this problem. With rounds of discussion with another two potential co-founders, we decide to develop the organization Make Waste Become Feast in January 2019 in the most dynamic Chinese city Shanghai. Combined with the market situation in China, we would like to start our business by two main approaches: helping the food providers to resell leftovers and recycling leftovers by donating to the charities where those food can be consumed afterwards. Our primary business partners will be catering places which include restaurants, hotels, and bakeries, from whom food leftovers are generated every day.